Moms' night out [videorecording (DVD)] - Erwin, Jonathan D.; Drew, Sarah, 1980-; Astin, Sean; Heaton, Patricia, 1958-; Adkins, Trace (Sony Pictures Home Entertainment, 2014)
All Allyson and her friends want is a peaceful, grown-up evening of dinner and conversation, a long-needed moms' night out. But in order to enjoy high heels, adult conversation, and food not served in a paper bag, they need their husbands to watch the kids for three hours - what could go wrong?